Transcript profiling of non-target-site imidazolinone resistance in imisun sunflower - Gil, Mercedes (2018)
Imidazolinone resistance found in a wild sunflower (Helianthus annuus L.) population was successfully transferred to a cultivated inbred line developing ‘Imisun’ sunflowers. Genetic regulation of this trait has been reported to involve two genes: Imr1, an allelic variant of ahasl1 locus that codes for acetohydroxyacid synthase catalytic subunit, and the modifier Imr2, whose identity remains unknown, but it could be related to non-target-site resistance such as xenobiotic metabolism. The aim of the present study was to characterize the gene expression of resistant and susceptible sunflower lines in response to imazethapyr herbicide by complementary DNA amplified fragment-length polymorphism (cDNA-AFLP). Three assays were performed to determine (i) optimal herbicide treatment concentration, (ii) duration of herbicide treatment, and (iii) in vitro acetohydroxyacid synthase activity to assess enzyme inhibition levels. An important number of genes related to metabolism of xeno-biotics and stress was found: cytochrome P450 monooxygenases, UDP-glucuronosyl/UDP-glucosyltransferases, glycosyltransferases, and ATP-binding cassette transporters, among others. These results suggest that non-target-site resistance mechanisms may contribute to herbicide resistance in Imisun sunflower and could be related to the modifier gene Imr2. Using cDNA-AFLP, we were able to detect candidate detoxification-related genes potentially involved in imidazolinone resistance in sunflower.